An Analysis of Maudy Ayunda's Code-Mixing and Code-Switching on The Merry Riana’s Podcast - Saragih, Ester; Pasaribu, Tiara Kristina; Sihite , Jubil Ezer (IKIP Siliwangi, 2025)
This research use code-switching and mixing, Merry Riana explores this in the audio episode